Research on Four Core Fiber WDM Device Technology - CHEN Li; XIAO Qingming; WANG Min; JIANG Lei (Guangtongxin yanjiu)
Space division multiplexing technology is one of the effective ways to improve the transmission capacity of optical communication system. The main technologies include Multi Core Fiber (MCF), few mode multiplexing and orbital angular momentum multiplexing, among which MCF technology is a mature one.【Objective】To solve the problem of capacity limitation in optical communication system, this article designed and developed a new four-core Wavelength Division Multiplexing (WDM) original sample.【Methods】Firstly, the technology of WDM, air division multiplexing, MCF and multicore fiber coupling is analyzed. The four core fan-in fan-out device made with capillary, lens and etch fiber is selected as the medium. Then, by combining MCF technology and WDM technology, starting from the selection of four-core fiber, the debugging principle and debugging method of four-core WDM, a new four-core WDM original sample is designed and developed by using four-core fan-in fan-out device. The index of the device is tested by using the difference method of four-core fan-in fan-out device.【Results】According to the test results of the experimental samples, the insertion loss of each reflection end and transmission end of the original four-core WDM 1 can be controlled within 0.8 dB, the isolation degree of each reflection end is >15 dB, and the isolation degree of each transmission end is ≥ 40 dB.【Conclusion】According to the test results, the following conclusions can be drawn: compared with the traditional single-core WDM scheme, the new four-core WDM can realize four-channel communication under the same device volume, and greatly improve the optical communication capacity. At the same time, it fills the gap in the research of air division multiplexing optical devices based on MCF technology and expands the application range of air division multiplexing, demonstrating the potential of multi-core fiber based long-distance transmission. WDM device based on space division multiplexing system has a wide application prospect in optical fiber communication system.